Histopathological studies of cardiac lesions after an acute high dose administration of methamphetamine - Molh, Arthur Kong Sn (PPSP, Universiti Sains Malaysia, 2007)
Male Wistar rats aged 6 weeks were injected intraperitoneally with methamphetamine hydrochloride in saline at a dosage of SO mglkg. The dosage of the drug used was determined to allow the rats to show signs of intoxication and to survive for 24 hours (Maruta et al., 1997). The rats were sacrificed and their hearts were collected to be studied for cardiac lesions under light microscopy. Hematoxylin and eosin staining, Masson's Trichrome stain and immunohistochemistry methods involving anti-myosin reagents were used to enhance visibility of changes in the myocardium. Five rats injected with methamphetamine hydrochloride died within four hours and their hearts were collected on the same day. Another rat survived for two days after injection of methamphetamine hydrochloride before being sacrificed. Microscopic examination of the myocardium of the rats that died on the same day injection did not show any of the expected sign of necrosis, with most test samples being non-discernible from the control samples, as the rats had died too soon after administration of the drug before the myocardium could develop any necrotic changes. However, there was Joss of nuclei in some myocytes in the sub-endocardium region, indicating cell deaths. Other areas in the sub-endocardium region also showed intemalisation and enlargement of myocyte nuclei, indicating regeneration of cells. There were very few foci of necrosis observed in these samples. The heart sample from the single rat that survived the injection for two days showed foci of infiltration of macrophage-like cells with large nuclei and little cytoplasm within the sub-endocardium layers, but they were subsequently identified as regenerating myocytes. Within these foci of cell infiltrations were also found macrophages and a few leucocytes. There was also presence of spindle-like fibroblasts, but the overall appearance of the myocardium does not indicate any inflammatory response of the cells. The expected signs of necrosis including eosinophilic changes and contraction band necrosis were not observed in this sample. These results suggest that there may be a need to re-evaluate the toxic and lethal dosages of methamphetamine for use in animals testing. The cause of death in these rats were suspected to be due to failure of other major organs from the acute dosage administration of methamphetamine, which may then indirectly caused heart failure, but death occurred within a time period where significant changes due to necrosis may not be evident in the myocardium. Thus, further testing procedures such as examination of changes in other major organs and detection of serum levels of methamphetamine may be necessary to help detect deaths due to acute intake of methamphetamine. The use of electron microscopy in conjunction with light microscopy is also recommended, as they will allow clearer differentiation of the necrotic changes in myocardium or other major organs.